Capsule endoscopy transit-related indicators in choosing the insertion route for double-balloon enteroscopy: a systematic review - Cortegoso Valdivia, Pablo; Skonieczna-Żydecka, Karolina; Pennazio, Marco; Rondonotti, Emanuele; Marlicz, Wojciech; Toth, Ervin; Koulaouzidis, Anastasios (Endoscopy International Open, 2021)
Background and study aims When capsule endoscopy (CE) detects a small bowel (SB) target lesion that may be manageable with enteroscopy, the selection of the insertion route is critical. Time- and progression-based CE indices have been proposed for localization of SB lesions. This systematic review analysed the role of CE transit indicators in choosing the insertion route for double-balloon enteroscopy (DBE).Methods A comprehensive literature search identified papers assessing the role of CE on the choice of the route selection for DBE. Data on CE, criteria for route selection, and DBE success parameters were retrieved and analyzed according to the PRISMA statement. Risk of bias was assessed through the STROBE assessment. The primary outcome evaluated was DBE success rate in reaching a SB lesion, measured as the ratio of positive initial DBE to the number of total DBE.Results Seven studies including 262 CEs requiring subsequent DBE were selected. Six studies used time-based indices and one used the PillCam Progress indicator. SB lesions were identified and insertion route was selected according to a specific cut-off, using fixed landmarks for defining SB transit except for one study in which the mouth-cecum transit was considered. DBE success rate was high in all studies, ranging from 78.3 % to 100 %. Six of seven studies were high quality.Conclusions The precise localization of SB lesions remains an open issue, and larger studies are required to determine the most accurate index for selecting the DBE insertion route. In the future, 3 D localization technologies and tracking systems will be essential to accomplish this tricky task.